Pengaruh Sensation Seeking terhadap Internet Gaming Disorder pada Gamers Usia 16-24 Tahun - Farhan Fauzan; Lilim Halimah (UNISBA Press, 2023)
Abstrak. The advancement of technology has rendered the realm of online gaming increasingly diverse and addictive. The emergence of new genres in online gaming has led individuals to become highly engaged in each game, thus risking the development of internet gaming disorder. Personality traits contribute to addiction, and one personality trait that is related to online gaming issues is sensation seeking. Various studies have found a correlation between these two variables. This study aims to determine the influence of sensation seeking on internet gaming disorder among gamers aged 16-24 in the Valorant community in Indonesia. The sample size taken from this community amounted to 122 individuals. The measurement tools used were the Internet Gaming Disorder Scale and the Brief Sensation Seeking Scale-1. Data analysis was conducted using multiple linear regression. The results of the statistical test indicate that the aspects within sensation seeking have a simultaneous influence with an R2 value of 0.255, meaning they contribute 25.5% to internet gaming disorder. Specifically, the aspects that have an impact on internet gaming disorder are experience seeking and disinhibition, each with an influence of R2= 0,906 and R2= 0.914, respectively. Abstrak. Perkembangan teknologi membuat ranah game online menjadi semakin variatif dan adiktif. Kehadiran genre-genre baru dalam game online membuat individu menjadi semakin terlibat tinggi dalam tiap permainannya sehingga berisiko mengalami internet gaming disorder. Trait kepribadian memiliki kontribusi terhadap adiksi, salah satu trait kepribadian yang berhubungan dengan permasalahan games online adalalah sensation seeking. Ragamnya penelitian yang telah dilakukan menemukan bahwa kedua variabel ini mempunyai hubungan. Penelitian ini bertujuan untuk mengetahui pengaruh sensation seeking terhadap internet gaming disorder pada gamers usia 16-24 tahun di komunitas Valorant Indonesia. Sampel yang diambil dari komunitas tersebut berjumlah 122 orang. Alat ukur yang digunakan adalah Internet Gaming Disorder Scale dan Brief Sensation Seeking Scale-1. Analisis data menggunakan regresi linier berganda. Hasil uji statistik menunjukkan bahwa secara simultan aspek – aspek dalam sensation seeking memiliki pengaruh dengan nilai R2 = 0,255 artinya berkontribusi sebesar 25,5% terhadap internet gaming disorder. Secara parsial, aspek yang berpengaruh terhadap internet gaming disorder adalah experience seeking dan disinhibition dengan masing – masing pengaruh sebesar R2= 0,906 dan R2= 0,914.